Kejadian Stunting Berhubungan dengan 8 Aksi Konvergensi - Yuliana Yuliana; Hasanudin Nuru; Berlian Kando Sianipar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to see the relationship between 8 stunting reduction convergence actions with stunting events in the Musi Rawas Health Office area of South Sumatra Province. The method used in this study is the cross-sectional method. The results showed that from the logistic regression test, it was found that there was a relationship between situation analysis (p-value = 0.0200), activity plans (p-value = 0.0015), stunting consultation (p-value = 0.0014), regent regulations on stunting (p-value = 0.0014). value=0.0017), human development cadre development (p-value=0.0025), data management system (p-value=0.0008), measurement and publication (p-value=0.0007), and annual performance review (p-value=0.0058) with stunting. In conclusion, 8 (eight) stunting reduction convergence actions are related to stunting incidence. Keywords: Stunting, 8 Convergence Actions